不一样的移民社会 ：黄乃裳组织福州人迁移诗巫的历史个案研究 = A different immigrant society : a study on Wong Nai Siong planned migration of Foochownese to Sibu - 陈雯 Chen, Wen (Nanyang Technological University, 2021)
华人移民海外的历史广为人知，但人们对华人移民的普遍印象都是较为负面的。一般认为华人移民在迁移地必定吃尽苦头才能在南洋生存下来，而从一般的影视或小说作品里面也多强调华人移民迁移过程的困苦经历以及在迁移地的不易。不过，这并不能代表所有的华人移民在迁移过程以及在迁移地都遭遇过坎坷的经历。二十世纪初，福州人在黄乃裳的带领下迁移到砂拉越诗巫。以集体移民的方式来到诗巫开辟垦场，这不但在砂拉越史上从未有过，在海外华人史上也是首开先例。华人移民移居海外均属于个人行动，至于“新福州”的移民则是有计划、组织性、且以大规模集体移民的方式，并与殖民政府签订移民合同，系统化地建立一个大面积的垦殖区。因此，这也使“新福州”移民与一般人们认知中的华人移民形成了鲜明的对比，同时“新福州”移民的特点也对其社会发展产生了深远的影响。本文将通过黄乃裳组织福州人迁移诗巫的历史个案，探讨“新福州”移民的特点，揭示华人移民较少为人知的一面，来打破一般人们对华人移民的既定印象。同时，也通过“新福州”移民的特点探讨其特点对“新福州”移民社会所产生的影响。The history of Chinese immigrants and immigration has been studied by many, and the impression for this history is mainly deemed in a negative light. It is generally believed that the Chinese immigrants will have to been through a bumpy journey while immigrating, and will have to face a lot of hardships, struggling to survive in Nanyang. Films and novels would also emphasize and portray such difficulty and struggle in the immigrating setting. Nonetheless, this is not the only representation of the whole immigration process. In the beginning of the 20th century, Wong Nai Siong led a group of Foochownese to move from Foochow to Sibu in Sarawak and opened up a reclamation site in the form of collective immigration. This is not only unprecedented in the history of Sarawak, but also in the history of overseas Chinese and Chinese immigration. Unlike most immigration plans, this is not a personal action. This plan, “new Foochow", signed an immigration contract with the local government, organized in a large-scale collective way, and established a large reclamation area systematically. Theses difference creates a contrast with the general history impression for the Chinese immigrants as recognized by the majority. Hence, the characteristics of "new Foochow" immigrants have a far-reaching impact on the social development of Chinese immigrants, which is worth exploring. This paper will discuss the characteristics of "new Foochow" immigrants, unfold the other light of the Chinese immigration history, and to offer another point of view and impression for the history of Chinese immigrants. It will also explore on the impact of the immigrant society through the characteristics of “new Foochow”.